The Effectiveness ASEAN Political Security Community (APSC in The Implementation of ASEAN Convention on Counter Terrorism (ACCT) to Combat Terrorism in Southeast Asia - Darmayadi, A; Ibrahim, A; Clariza, W L (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This research aims to explain the effectiveness of the ASEAN Political-Security Community (APSC) in implementing the ASEAN Convention on Counter-Terrorism (ACCT) to combat terrorism in Southeast Asia. Using qualitative research methods and data collection techniques, literature studies through various scientific works to understand and study the phenomena that will be discussed in this journal. Researchers see the potential and strength possessed by APSC in implementing ACCT in Southeast Asia. However, the existence of the ASEAN Way will complicate the implementation of the ACCT itself. Coupled with evidence on acts of terrorism in the Philippines, ACCT under the auspices of the APSC has not been able to stop the issues. The researcher also examines how each terrorist group ends, presenting that terrorist groups end up using regulation from the country itself through the domestic police, without regulatory interference from international organizations. In conclusion, the APSC has played a crucial role in enhancing regional cooperation and coordination to combat terrorism in Southeast Asia. The establishment of the ACTC and the adoption of common strategies and policies have been significant achievements in the implementation of the ACCT. However, more needs to be done to address the challenges and ensure consistent and effective enforcement of counter-terrorism laws across ASEAN member states.